From external success to inner peace: integrating Bhagavad Gita teachings into higher education - Raj K. Baral; Pradip Raj Giri (Cogent Education)
The western epistemological tradition often encourages the pursuit of ‘happiness’ in the external world. However, such an approach overlooks issues like internal conflict, dissociation of the self, and broader social-political-cultural disconnection. This article examines these limitations and proposes the integration of the essence of the Gita’s teachings into higher education as a complementary epistemological and pedagogical framework. Drawing on textual analysis approach, the article identifies core principles such as inner peace, karma yoga, and spiritual well-being as meaningful counterbalance to the west’s focus on external success. It proposes three practical pathways for practical integration: curricular design, pedagogical transformation, and epistemic intervention. The findings contribute to the discourse on ethical and spiritually grounded education by advancing Bharatavarshiya rhetorical and philosophical framework that values both personal and societal well-being.